Enhancement of oxidative stability and cold flow properties of coconut oil using natural antioxidant additives for development of bio-lubricant. (April 2021) - Kumar, S Anoop; Suresh, Gautham; Hariprasad, V; Deepak, GS; Akhil, PS
Coconut oil is less preferred for lubrication purposes, particularly, in high-temperature applications, due to their low thermal stability. Chemical additives for improvements tend to make coconut oil less bio-sustainable and more hazardous. Using natural antioxidants for enhancing oxidative stability has been successfully implemented in food industry. The present study investigates the application of three natural additives – ginger, black pepper and garlic, as possible substitutes for chemical additives in enhancing lubrication properties of coconut oil. In addition to enhancing thermal stability, these natural additives mixed in small proportions could help bring down pour point of coconut oil. Adding traces of food additive, propylene glycol, lubricant samples showed impressive performance in terms of viscosity, friction and wear.